RESILIENSI AKADEMIK PADA SISWA SMPN 08 TAMBUN SELTAN PASCA PANDEMI COVID-19 DITINJAU DARI JENIS KELAMIN: Nabila Nurika Utada, Yulia Fitriani, Yuarini Wahyu Pertiwi - Nabila Nurika Utada; Yulia Fitriani; Yuarini Wahyu Pertiwi (Social Philanthropic, 2023)
This research was conducted to find out whether there is a difference between the academic resilience of students at SMPN 08 Tambun Selatan after the Covid-19 Pandemic in terms of gender. The subjects in this study totaled 150 students consisting of 75 male students and 75 female students. The sampling technique uses quota sampling. The data analysis technique uses a different test, namely the Independent Sample t Test. Based on the results of data analysis using SPSS 23, a Sig p value of 0.981 (p> 0.05) was obtained with a mean value of 86.3200 for male students and 88.7067 for female students. The conclusion of this study was that there was no difference between the academic resilience of male students. male and female students.